»At tale med de døde ....« Om sækularisering og hermeneutik i Kaj Thanings forfatterskab - Nielsen, Mikkel Crone (Grundtvig-Studier, 2002)
»At tale med de døde ...« Om sækularisering og hermeneutik i Kaj Thanings forfatterskab. Bibliografi over Kaj Thanings forfatterskab [»Talking with the dead« - On secularisation and hermeneutics in the writings of Kaj Thaning] By Mikkel Crone Nielsen Kaj Thaning’s thesis that Gr.’s visits to England 1829-31 led to his »conversion to life« and emergence as advocate of ‘secularisation’ has proved both influential and controversial, as has his methodological approach to the interpretation of Gr.’s writings with its underpinning thesis that Gr.’s entire literary production is determined by the one basic problem: how the relationship between human life and Christianity is to be understood. Raised in a Grundtvigian and clerical family, Thaning overtly personalized the theological issues that involved him. From 1922 onwards he was an activist in the Danish student-Christian association (Danmarks kristelige Studenterforbund), which was to voice through the periodical Tidehvery a radical criticism of the inward-turned and exclusive character of contemporary Danish congregational life, which judgmentally isolated itself from those powerful secular movements going on within national life as a whole. He held that it was not the true nature of the gospel, and therefore not the proper business of the Church, to exercise a judgmental power over the secular world. Rather, the congregation instead of clinging to ‘churchliness’ should provide an open place among the people where the gospel, which is for all the people, was proclaimed. The Church must be willing to risk a weakening of Christianity’s spiritual influence in this desirable process of ‘secularisation’. Believing that such ‘secularisation’ was entirely within the spirit of Gr. himself, contrary to the received ‘myth’ of Gr., Thaning proposes (1941) to »work with Gr. in his workshop« - to follow Gr. through his successive writings, as he hammered out his beliefs. Thus he analyses Gr.’s confrontation with himself (opgør med sig selv) in the wake of the England-visits, the outcome of which was Gr.’s rejection of German idealism in favour of an antiidealistic, common-sense thinking which Thaning calls ‘realism’. In the introduction to his Nordic Mythology (1832), Gr. moves towards prioritizing the human experiencing of existence in this world, here and now, over the cultivation of an empowered Christian religion, and towards seeing Christianity as endorsing rather than opposing this existential engagement with the life given in creation and with the moment. Charged by his critics with applying modem existentialist theological concepts alien to Gr., Thaning defends the concept ‘secularisation’ which he has adopted from Friedrich Gogarten - though he can be shown to have trodden his own independent path, especially in that, where Gogarten derives his justification from the Christian faith itself, Thaning derives his from a recognition of the innate worth of created human life without necessary reference to the Christian religion. The Christian gospel disavows any apologetic intention or any imposition of authority over its adherents, and God’s word must wander the world homeless. Redemption is to be understood in terms of the freeing of created human life from its shackles - the very shackles which gnosticism would lay upon human beings, namely utter disavowal and rejection of the world and the human experiencing of it. The critique of religion informing Thaning’s writings is primarily directed against such gnosticism - which he calls ‘pilgrim-Christianity’ (pilgrimskristendom) - as it thrives in latter-day Lutherdom. Gr. is himself aware of his role as a father of such ‘secularisation’ and Thaning, following him, is prepared to find the starting-point for his own ‘secularisation-theology’ even in ‘heathen’, non-Christian human life, because this is what life demands. Central to Thaning’s interpretative method is the assumption that historical distance between an author and a commentator can be bridged when the issue is one of common human existential experiencing. With Rudolf Bultmann (and behind him, Heidegger), Thaning accepts that the neutrality of a systematic, objective analysis is thus relinquished in favour of an existential interest in the shared situation addressed. The exegete meets the text with his own premises in mind, expecting that the text will then cast new light upon them. Thus a dialogue is validated; but subjective arbitrariness in the exegete is constrained by adherence to »a formal anthropology and an existential analysis«. Thaning’s understanding of that life given to human beings in creation is greatly indebted to the religious-historical writings of Vilhelm Grønbech, who in particular rejects the distinctively European concept of human life as a pilgrimage through an imperfect world to the perfection of the heavenly homeland, along with its resultant dualistic perception of a true, spiritual self engaged in a struggle with the natural self. Herein, Thaning perceives not just a European but a universal and historical conflict between religion and human life, which stance furnishes him, in practice, with a theological hermeneutic. Thus Thaning engaged in a generational confrontation with a certain traditional Grundtvigian conceptualisation of the Christian congregation. Though he made little overt declaration of his hermeneutical method, he worked with discernible controlling concepts and brought to the task an enormous knowledge of Gr.’s writings. Accordingly he made an unparalleled impact upon Gr. studies and his work stands as an indispensable reference-point in Gr. research.